Chapter 18 - Gliadins in foods and the electronic tongue - Veloso, Ana C. A. (2016)
The commercialization of safe foods is a main concern and should be ensured throughout the entire food supply chain. So, fast, sensitive, and reliable analytical methods are needed to identify food-related specific hazards, ensuring consumers protection and avoiding health problems. This chapter is focused on the emerging (bio)sensors to detect the heat-stable allergen gliadin in gluten-free foods. A brief overview concerning gliadin and its relation to celiac disease is provided. Several works related to the development of biosensors for gliadin detection are presented. Moreover, the use of electronic tongues to detect gliadin or gluten is reviewed and further investigated in an attempt to explain the possible detection mechanism based on gliadinlipid membranes interactions. The challenges, concerns, and potential application of these (bio)sensors are discussed. Finally, some future perspectives are included regarding the applicability of electronic tongue within this research field.